Inserting Stipulation Pertaining to Polygamy in a Marriage Contract in Muslim Countries - Raihanah Abdullah (Al-Jami'ah Research Centre, 2008)
Generally, Islam permits a wife to stipulate any conditions in a marriage contract. The Muslim jurists however differed in determining the validity of certain conditions and terms upon which their marriage is to take place. One of the controversial conditions is that the wife includes a condition pertaining to polygamy in the marriage contract. It is interesting to note that the practice of inserting stipulations pertaining to polygamy is not a new practice or unusual among many Muslims in the Middle East. Therefore, this article seeks to discuss the possibilities to adopt the Hanbalite’s principles on this matter in muslim countries where the Shafi’ite school of thought is predominantly followed. This article argued that by allowing the wife to insert stipulations pertaining to polygamy in a marriage contract does not go against Islam. This is because stipulations in the marriage contract are often aimed at preventing such eventuality and also protecting the position of women should it come to prevent.